Dated phylogenies and historical biogeography of Dontostemon and Clausia (Brassicaceae) mirror the palaeogeographical history of the Eurasian steppe - Friesen, Nikolai; German, Dmitry; Hurka, Herbert; Herden, Tobias; Oyuntsetseg, Batlai; Neuffer, Barbara (Journal of biogeography, 2016)
Aim We hypothesize that molecular signals in Eurasian steppe plants reflect their biogeographical history as well as the climate/landscape history of the Eurasian steppe. To test this hypothesis we focus here on the characteristic Eurasian steppe genera Dontostemon and Clausia (Brassicaceae), and have included all presently accepted species in our study. Location Eurasian steppe from eastern Asia to south-eastern Europe. Methods To elucidate their phylogeny, we sequenced the nuclear ribosomal ITS and chloroplast trnL-F regions. Sequence data were analysed with parsimony and Bayesian phylogenetic approaches. Divergence times were estimated using BEAST, relying on published ITS substitution rates. Distribution maps of all species of the two genera were compiled, and ancestral areas reconstructed using LAGRANGE. Results Both genera originated in central and eastern Asia, with Clausia later extending its range to eastern Europe. Dated phylogenies revealed: onset of diversification in the lower and middle Miocene; evolution of the majority of groups in the upper Miocene/lower Pliocene, and further speciation events during the Quaternary. Origin and diversification within these genera coincide with the evolution and history of the modern Eurasian steppe. Main conclusions Dated phylogenies and historical biogeography of Clausia and Dontostemon mirror the climate/landscape dynamics of the steppe from its origin in the early Miocene up to the Pleistocene and Holocene.
First published: 11 December 2015
Gesehen am 27.05.2020